Effect of different ashes from biomass olive pomace on the mechanical and fire properties of gypsum-based materials - Peceño, Begoña; Pérez-Soriano, Eva M.; Ríos, Jose D.; Luna, Yolanda; Cifuentes, Hector; Leiva, Carlos (Revista de la Construcción. Journal of Construction, 2023)
In this study, biomass ashes from different energy valorization processes and storage conditions were used to make fire-resistant materials. Some of the ashes were subjected to a carbonation process. An 80/20 ash/gypsum ratio was used in all compositions. The density and different mechanical properties (compressive and flexural strength, superficial hardness, and dynamic modulus of elasticity), as well as fire resistance properties (insulating capacity and heat absorption capacity), were evaluated at 28 days. The energy valorization had a great influence on the particle size and the Loss On Ignition (LOI) of the fly ash. By increasing both, materials with lower mechanical properties (90%) were produced. Fire resistance was similar for the different ashes tested, but 50% lower than the gypsum material. When the ashes of the materials were carbonated, the material increases compressive strength by 400% compared to ashes without the carbonation process, and the fire resistance was similar to those materials composed exclusively of gypsum, but also a source of CO2 capture is produced.